RESEARCH OF STRUCTURE AND PROPERTIES OF PROTEINS OF LOCAL VARIETIES OF LENTIL GRAIN - Yormatova Dilorom Yormatovna; Majidov Kakhramon Khalimovich; Majidov Kakhramon Khalimovich (Journals Park Publishing, 2022)
Physical-chemical and functional properties of the protein isolate from lentil grains have been determined. The conformational structure of protein molecules has been determined by IR spectroscopy. It has been established that protein isolates retain their native state during deep processing.
Keywords: lentil grains; protein isolate; structure